Paracrine renal endothelin system in rats with liver cirrhosis. - Hocher, B. (1996)
1. Liver cirrhosis was induced in rats by CCl4 administration. We analysed the expression of endothelin receptor subtypes in the renal cortex and medulla using Scatchard analysis and receptor autoradiography, and measured plasma as well as renal-tissue endothelin-1 concentrations using a specific radioimmunoassay. Furthermore, we analysed the effects of the non-selective (A/B) endothelin receptor antagonist, bosentan (6 and 100 mg kg-1 day-1) on mean arterial blood pressure, water and sodium excretion and glomerular filtration rate. 2. Our study revealed an overexpression of the endothelin B receptor (ETB) in the renal medulla of rats with liver cirrhosis (Cir: 2775 +/- 299 fmol mg-1; Con: 1695 +/- 255 fmol mg-1; n = 8; means +/- s.d., P < 0.01), whereas the density of ETB in the cortex and the endothelin A receptor (ETA) in the cortex and medulla were similar in both cirrhotic and control rats. Receptor autoradiography showed that the upregulation of medullary ETB in cirrhotic rats was due to an upregulation of ETB in the inner medullary collecting duct cells. 3. The tissue endothelin-1 concentrations were increased in the renal medulla of cirrhotic rats (Cir: 271 +/- 68 pg g-1wet wt.; Con: 153 +/- 36 pg g-1 wet wt., n = 8; means +/- s.d., P < 0.01). 4. The glomerular filtration rate was slightly decreased in cirrhotic rats but not altered after bosentan treatment in either cirrhotic or control rats. Bosentan decreased sodium excretion to a similar extent in both cirrhotic and control rats, whereas water excretion was significantly reduced by both dosages of bosentan in cirrhotic rats only (Cir + vehicle: 12.5 +/- 0.62 m day-1, Cir + 6 mg kg-1 day-1 bosentan: 8.6 +/- 1.0 ml day-1; Cir + 100 mg kg-1 day-1 bosentan: 7.4 +/- 0.6 ml day-1; n = 10; means +/- s.e.mean). 5. We therefore suggest that the upregulation of the medullary ETB in cirrhotic rats is involved in the regulation of water excretion in rats with CCl4-induced liver cirrhosis.